The mass-metallicity-kinematics relation of the stellar components of eagle galaxies - Zenocratti, Lucas Jesús (2021)
In this work, we study the stellar mass - stellar metallicity relation as a function of the morphokinematics of galaxies in EAGLE cosmological simulations. According to our findings, at a given stellar mass (Ai*), stellar metallicity shows a secondary dependence on the morpho-kinematics of galaxies, which is more evident towards high masses. At the high-mass end (Μ* > 1010 Mq), dispersion-supported systems show lower metallicities, on average. In addition, low-mass galaxies with higher rotational support are somewhat more metalpoor. More massive galaxies tend to exhibit flatter morphologies, being prolate systems less metal-enriched, on average. As the redshift z increases, those aforementioned dependences of metallicity on kinematics and morphology tend to become stronger at high masses. These trends are consistent with the dependences of the stellar mass - gas-phase metallicity relation on gas fraction, star formation rate and stellar age, and the relation of the latter quantities with galaxy morpho-kinematics.